Blue is the sea. - López-Ibor, Sofía, ....- (San Francisco : Pentatonic Press, 2011)
Music teacher Sofia Lopez-Ibor addresses the concept of arts integration using a basic approach for the music and dance classroom. This book features 25 themes with music, poetry, dance and visual arts activities for preschool through middle school students. The activities intend to develop intuition, observing skills, sensorial experiences and inner-growth. This unique book includes: > Lesson examples applicable to students of all ages > Pedagogical and methodological ideas for teaching music and visual arts > Games, songs and poems with body percussion and orchestrations for the Orff ensemble > Movement exploration and improvisation exercises > Suggestions for illustrating texts and songs > Graphic Notation scores > Tips for observing art Examples of student art and poetry The ideas in the book can be used by Orff practitioners, art specialists and general classroom teachers. The visual art projects can be used in a music class as a way to introduce a theme or end a session. Most of the songs, rhymes and dance activities are simple enought to be led by a non-music instructor. There are also models of collaboration with your fellow teachers, researching, planning projects and sharing ideas. Contents > MUSIC, MOVEMENT AND ART > GRAPHIC NOTATION > CONNECTING IMAGE TO MUSIC, ART AND POETRY > MUSIC LISTENING AND THE VISUAL ARTS
Keywords: Beeldende expressie; Dramatische expressie; Muzikale expressie; Verbale expressie